Aesthetic Disinterestedness in Neuroaesthetics: A Phenomenological Critique - Fotini Vassiliou (Aesthetic Investigations, 2020)
In recent neuroaesthetic discussion, neuroscientists have linked aesthetic pleasure to the brain’s reward systems, but they have also attempted to dissociate it from utilitarian rewards and ultimately explain it as a disinterested state of mind. This paper examines this neuroaesthetic approach, juxtaposing it with elements of phenomenological thought on the subject of aesthetic disinterestedness, to present three interrelated concerns that can be raised from a phenomenological perspective, as well as to outline how to overcome these problems phenomenologically. The paper ends with the suggestion that neuroaesthetics, if it is ever going to offer something important or useful regarding our understanding of aesthetic experience, has to become phenomenologically sensitive and informed.